THE INFLUENCE OF DIGITAL AND FINANCIAL LITERACY BEHAVIOR TOWARDS CONSUMPTIVE SHOPPING BEHAVIOR ONLINE IN GENERATION Z IN PANANRANG VILLAGE - Ramadhani, Amalia; Muhammadun, Muzdalifah; Arwin (Institut Agama Islam Negeri Parepare, 2025)
The purpose of this study is to describe whether digital financial literacy has an effect on consumptive spending behavior Online in Generation Z. describes whether Financial Behavior Affects Shopping Consumptive Behavior Online in generation Z. This type of research uses quantitative methods. Saturated sampling is used to distribute questionnaires to Generation Z to obtain data. The two forms of data analysis used in this study are multiple regression analysis and descriptive analysis approach. The data processing in this study uses IBM SPSS Statistics 26. The results of the study show that: First, the results of the t-test hypothesis test (Partial) show that the significance value for the X1 variable is 0.04 < 0.05 and the t-calculation value is -2.960 < t-table 1.985 so that it is stated that digital financial literacy has a significant effect on spending consumptive behavior Online with the direction of the negative relationship, the second based on the hypothesis test of the t-test (partial) shows a significant value for the variable X2 of 0.00 < 0.05 with a t-calculated value of 12.530 < t-table 1.985, so it can be stated that Financial Behavior Have a significant effect on consumptive shopping behavior Online with the direction of positive relationships. The F value is calculated as 78.929 > F table 3.09 so that it is stated that there is an influence of variable X on variable Y together (simultaneously). Conclude that the hypothesis in this study is accepted, namely that there is an influence of digital financial literacy variables and Financial Behavior on consumer spending behavior Online generation Z in Pananrang Village, Mattiro Bulu District, Pinrang Regency.